The Predictive Role of Grapho-Morphological Knowledge in Reading Comprehension for Beginning-Level L2 Chinese Learners - Chen, Tianxu; Ke, Sihui; Koda, Keiko (Frontiers in Psychology, 2021)
Reading comprehension entails a set of distinct, yet interdependent cognitive, linguistic, and nonlinguistic processes. Previous second language (L2) Chinese studies have identified significant and positive impacts of grapho-morphological knowledge at the character and subcharacter (radical) levels on passage reading comprehension; however, little is known regarding how early L2 grapho-morphological knowledge at the character and radical levels jointly predict later L2 reading comprehension. This study aimed to fill this gap. One hundred and five beginning-level L2 Chinese collegiate learners were recruited, and completed two character-related and two radical-related tasks in Week 8, as well as one reading comprehension tasks in Week 18. The main findings, based on correlational and path analyses, suggested that L2 Chinese learners’ early character-level and radical-level grapho-morphological knowledge significantly predicted later reading comprehension, yet the interrelations among grapho-morphological knowledge at the character and radical levels were complex. Path analyses identified direct and indirect paths from early character-level grapho-morphological knowledge to later reading comprehension, as well as indirect paths from early radical-level grapho-morphological knowledge to later reading comprehension. Methodological and pedagogical implications for L2 Chinese reading research and practices are discussed.